Rancang Bangun Aplikasi Manajemen Barang Daerah Berbasis Web Pada Dinas Pendapatan Jawa Timur - Yogie, Akhmad; Arifin, Mochammad; Erstiawan, Martinus Sony (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
abstract:Â Department of Revenue is a provincial government agency engaged in the implementation of the collection of local taxes and levies. With a wide working area, the Department of Revenue has a working area with seconded by 38 Technical Implementation Unit (UPT) and 42 System Administration Manunggal Of One Roof (SAMSAT) spread in East Java. UPT and SAMSAT has the task to carry out some tasks in the Office of operational techniques local revenue collection, administration and services. asset management processa that has been happening is part of equipment trouble collecting goods data area are scattered in every unit and SAMSAT because officers maid still use the flashdrive as a medium to deliver data to the department that led to waiting for the required data and could cause delays to your reporting needs . Based on these problems, the authors make the application of web-based management area goods so as to reduce costs and shorten delivery time of data from flash and reports can be generated quicklyÂ